Characterization of Iron Accumulation in Deep Gray Matter in Myotonic Dystrophy Type 1 and 2 Using Quantitative Susceptibility Mapping and R2* Relaxometry: A Magnetic Resonance Imaging Study at 3 Tesla - Ates, Sevda; Deistung, Andreas; Schneider, Ruth; Prehn, Christian; Lukas, Carsten; Reichenbach, Jürgen R.; Schneider-Gold, Christiane; Bellenberg, Barbara (Frontiers in Neurology, 2019)
Quantitative mapping of the magnetic susceptibility and the effective transverse relaxation rate (R2*) are suitable to assess the iron content in distinct brain regions. In this prospective, explorative study the iron accumulation in deep grey matter nuclei (DGM) in myotonic dystrophy type 1 (DM1) and 2 (DM2) and its clinical and neuro-cognitive relevance using susceptibility and R2* mapping was examined. Twelve classical DM1, four childhood-onset DM1 (DM1c.o.), twelve DM2 patients and twenty-nine matched healthy controls underwent MRI at 3 Tesla, neurological and neuro-cognitive tests. Susceptibility, R2* und volumes were determined for eleven DGM structures and compared between patients and controls. Twelve classical DM1, four childhood-onset DM1, and 12 DM2 patients as well as 29 matched healthy controls underwent MRI at 3 Tesla, and neurological and neuro-cognitive tests. Susceptibility, R2* and volumes were determined for 11 DGM structures and compared between patients and controls. Iron accumulation in DGM reflected by R2* or susceptibility was found in the putamen and accumbens of DM1 and in DM2, but was more widespread in DM1 (caudate, pallidum, hippocampus, subthalamic nucleus, thalamus and substantia nigra). Opposed changes of R2* or susceptibility were detected in caudate, putamen and accumbens in the childhood-onset DM1 patients compared to classical DM1. R2* or susceptibility alterations in DGM were significantly associated with clinical symptoms including muscular weakness (DM1), daytime sleepiness (DM1), depression (DM2) and with specific cognitive deficits in DM1 and DM2.